Galectin-9: diverse roles in skin disease - Lin Wang; Lin Wang; Chuqiao Zhang; Jiang Ji; Qingqing Jiao; Qingqing Jiao (Frontiers in Allergy, 2025)
Galectin-9 (Gal-9) is a multifunctional immunomodulatory molecule involved in cell growth, differentiation, adhesion, communication, and death. Galectin-9 mediates its physiological functions through interactions with multiple membrane receptors, including T-cell immunoglobulin mucin-domain containing-3 (Tim-3), immunoglobulin E, and the hyaluronan receptor CD44. In recent years, Gal-9 has been extensively studied in autoimmune diseases, tumor microenvironments, and viral infections. The circulating levels of this lectin demonstrate clinical correlation with disease progression in both acute and chronic infectious conditions. In addition, Gal-9 can potentially be a reliable, sensitive, and noninvasive biomarker of disease severity in many skin diseases. However, there has not been a review of Gal-9 studies in patients with dermatosis. This review summarizes recent advances in understanding Gal-9's immunomodulatory mechanisms in chronic spontaneous urticaria pathophysiology, systemic lupus erythematosus, atopic dermatitis, melanoma, systemic sclerosis, herpes simplex virus infection, bullous pemphigoid, psoriasis, vitiligo, maculopapular exanthema, and skin grafting to provide a reference for future research. Gal-9 is an important regulator of immune homeostasis whose level changes significantly in many skin diseases, and validation was performed in a mouse model using exogenous Gal-9. Ongoing studies are necessary to clarify the pathophysiology of Gal-9, identify the potential of Gal-9 as a new biomarker, and develop new therapeutic approaches for skin diseases.